2019
DOI: 10.1371/journal.pone.0212404
|View full text |Cite
|
Sign up to set email alerts
|

Combination of colonoscopy and magnetic resonance enterography is more useful for clinical decision making than colonoscopy alone in patients with complicated Crohn's disease

Abstract: Background/aims The small bowel is affected in more than half of patients with Crohn’s disease (CD) at the time of diagnosis, and small bowel involvement has a negative impact on the long-term outcome. Many patients reportedly have active lesions in the small intestine even in patients in clinical remission. This study was performed to compare findings of magnetic resonance enterography (MRE) and ileocolonoscopy. Methods A single-center retrospective study was conducted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 39 publications
0
4
1
Order By: Relevance
“…However, no significant association was found between the inflammatory or fibrostenosing criteria in MRE and disease activity based on ileocolonoscopy. These findings differ from those in a retrospective study by Sagami et al, who reported a positive correlation between the SES-CD and the MaRIA scores in patients with inflammatory activity, while no correlation was found in individuals with fibrostenosing or penetrating disease [39]. Although our work presents a relatively small number of patients with exclusively proximal CD, these divergent findings in the literature may be due to a high incidence of terminal ileal disease in topography possibly not accessible by colonoscopy.…”
contrasting
confidence: 99%
“…However, no significant association was found between the inflammatory or fibrostenosing criteria in MRE and disease activity based on ileocolonoscopy. These findings differ from those in a retrospective study by Sagami et al, who reported a positive correlation between the SES-CD and the MaRIA scores in patients with inflammatory activity, while no correlation was found in individuals with fibrostenosing or penetrating disease [39]. Although our work presents a relatively small number of patients with exclusively proximal CD, these divergent findings in the literature may be due to a high incidence of terminal ileal disease in topography possibly not accessible by colonoscopy.…”
contrasting
confidence: 99%
“…Balloon-assisted endoscopy, in addition to MRE, may be beneficial if the patient has obstructive symptoms as indicated in statement 3.3 [ 185 ]. Unfortunately, in patients with stricturing disease, SES-CD based on conventional ileocolonoscopy does not correlate with MaRIA score nor does it predict the need for treatment escalation, [ 186 ]. This is likely because the stenosis prevents deep insertion of the scope for many patients, thereby limiting the ability of endoscopy to assess inflammation.…”
Section: Consensus Recommendationsmentioning
confidence: 99%
“…57 In a retrospective study of 50 CD patients, MRE findings indicated the need for treatment modification in 24% of patients who had endoscopic remission defined by a SES-CD <5. 58 MRE can be used in diagnosing small bowel inflammation and as well as a prognostic tool for relapses, 59 therefore it has found its place in monitoring CD patients.…”
Section: Cross Sectional Imaging Monitoringmentioning
confidence: 99%